DEKONSTRUKSI KONSEP MUTU PENDIDIKAN ISLAM TINJAUAN KRITIS TEORI MANAGERIALISM DAN IMPLIKASINYA TERHADAP HUMANISASI PENDIDIKAN - Yudi Sahara (STKIP Pesisir Selatan, 2026)
This study aims to deconstruct the concept of quality in Islamic education, which has long been dominated by the paradigm of managerialism, and to analyze its implications for the humanization of education. The main focus of the study is to reveal the tension between managerial logic that emphasizes efficiency, standardization, and quantitative measurability, and the holistic objectives of Islamic education oriented toward the formation of faithful, moral, and civilized human beings. This research employs a qualitative approach within a critical–interpretive paradigm, using a library research method supported by field data in the form of interviews and observations conducted at MI Miftahul Huda Tugu Mulyo, Ogan Komering Ilir. Data analysis techniques include content analysis and critical analysis of reputable academic literature, policy documents, and empirical findings. The findings indicate that managerialism theory creates structural tensions with the holistic goals of Islamic education, reduces the meaning of educational quality to administrative achievements and quantitative indicators, and marginalizes the humanization of education as a quality indicator that is, in fact, crucial.